Correlation between lncRNA SNHG16 gene polymorphism and its interaction with environmental factors and susceptibility to colorectal cancer. Issue 48 (25th November 2020) - Zhou, Li; Zhang, Yuefeng; Jin, Jianjiang; Gu, Xuewei
Abstract: Objective: To study the relationship between long-chain non-coding RNA small nucleolar RNA host gene 16 (lncRNA SNHG16 ) polymorphisms and its interaction with environmental factors and susceptibility to colorectal cancer (CRC). Methods: Sanger sequencing was used to analyze genotypes of lncRNA SNHG16 gene rs7353, rs8038, and rs15278 sites. Multifactor dimensionality reduction was used to analyze interactions between lncRNA SNHG16 gene rs7353, rs8038, rs15278 sites, and environmental factors. Haploview 4.1 software was used to analyze linkage disequilibrium of lncRNA SNHG16 gene rs7353, rs8038, and rs15278 sites. Quantitative real-time polymerase chain reaction was used to analyze plasma lncRNA SNHG16 levels of CRC patients and control subjects. Results: Variation of the lncRNA SNHG16 gene rs7353 site A>G variation was associated with decreased CRC susceptibility (Odds ratio [OR] = 0.50, 95% confidence interval [CI]: 0.40–0.62, P  < .01). The rs8038 site G>A and rs15278 site A>G variation were associated with increased CRC susceptibility (OR = 1.87, 95% CI: 1.47–2.36, P  < .01). The rs15278 site G>A variation was associated with increased CRC susceptibility (OR = 2.24, 95% CI: 1.61–3.11, P  < .01). Interaction combinations featuring age, rs7353, rs8038, and rs15278 single nucleotide polymorphism are 13.53 times more susceptible to CRC than other interactions (95% CI: 9.43–19.41, P  < .01). The rs15278, rs8038, and rs7353 site AGA haplotypes were significantly associated with a decreased CRC risk (OR = 0.65, 95% CI: 0.48–0.88, P  = .01), AAG haplotypes were significantly associated with an increased CRC risk (OR = 2.00, 95% CI: 1.27–3.17, P  < .01). High lncRNA SNHG16 expression was associated with tumor progression in CRC patients (χ 2  = 8.85, P  = .03). The rs7353 site A>G variation caused a significant decrease in plasma lncRNA SNHG16 level ( P  < .01), while the rs8038 site G>A variation and rs15278 site A>G variation resulted in increased plasma lncRNA SNHG16 levels. Conclusion: Polymorphisms of lncRNA SNHG16 gene rs7353, rs8038, rs15278 loci and their interaction with age are significantly associated with CRC susceptibility.